Flexibility of the Application of Various Islamic Schools of Thought in Some Issues Relating to Hibah; Study on Provisions In Malaysian Law and Other Countries - Muda, Zulkifly bin (Jurnal Fiqh, 2006)
Hibah is a form of gift in the same category as hadiyyah and sadaqah. The article attempts to elaborate the concept of hibah in terms of its validity in the case of apostasy of the giver, its conditions and implementation pertaining to al-Mu'atah, al-Qadb and Marad al-Maut in several Islamic countries. The article also covers the with drawal of hibah and its legal procedures and implications. In the elaboration, cases are cited to indicate the implication and related problems.